SPECIES DISTRIBUTION OF DEER FEEDS (Muntiacus muntjak Zimmermann, 1780) AND ITS COMMUNITY COMPOSITION IN SERMO WILDLIFE RESERVE AREA, SPECIAL REGION OF YOGYAKARTA - Desti Rahmadian; Suhandoyo Suhandoyo; Sandy Nurvianto (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2023)
Muntiacus muntjak is a native Southeast Asian mammal, widely distributed in Sumatra, Bangka Belitung, Riau Islands, Java, Bali, Nusa Tenggara, and Kalimantan. Its existence is increasingly threatened by deforestation and habitat degradation. Habitat integrity and the sustainability of forest plant species as a source of feed for deer in the Sermo Wildlife Reserve area need to be maintained, in order to ensure the survival of these animals in their natural habitat. This research’s aims to determine the type of Muntiacus Muntjak feed, describe the distribution pattern of Muntiacus muntjak feed plant species and identify the composition of lower plants in Sermo Wildlife Reserve Area.The method wich used to quantify the structure and composition of vegetation types is systematic random sampling used 46 plots with measuring 1 m x 1 m and 2 m x 2 m for grass and lower plants datas as the material to epidermal analysis and the calculation of the total dry weight. Faecal analysis was conducted at the Wildlife Laboratory, Faculty of Forestry UGM. The distribution of deer feed plant species that have been identified will be processed using ArcView GIS 10.8 based on the coordinates where the feeds species found in Sermo Wildlife Reserve.The results showed that there were 19 species of lower plants identified as deer feed with uniform and clustered species distribution patterns. The community composition of lower plant species in Sermo Wildlife Reserve consists of 93 species from 49 different families.